From the concepts of meaning and reference to the concept of prototypicality - Assunção, Carlos (2022)
Meaning is a uniquely human phenomenon. In linguistics, this subject matter is especially complex, considering the multiplicity of theoretical approaches and the variety of disci plinary fields that address the issue. A similar concern applies to the concept of reference, because, although most linguists today agree that meaning and reference form two differ ent realities, the discussion about the relation between these two terms has not yet been fully examined. Cognitive Linguistics has made a great contribution to this discussion by recognizing that we cannot present the postulate of the existence of a level of meaning that belongs only to language and is distinct from the level at which the meaning of linguistic forms is associated with the knowledge of the world. The objective of this work is to show that, with Cognitive Linguistics, the ideas of meaning and reference are re-equated and have gained strength in the scope of linguistic studies reinforced by the concept of prototype. For such purpose this text describes the way these concepts have evolved based on their theorisation, paying particular attention to cognitive seman tics, but not intending to make an exhaustive theoretical-methodological analysis of them.